Medication adherence and its possible associated factors in patients with acne vulgaris: A cross‐sectional study of 200 patients in Iran. Issue 6 (20th October 2020) - Salamzadeh, Jamshid; Torabi Kachousangi, Samaneh; Hamzelou, Shahin; Naderi, Sina; Daneshvar, Elham
Abstract: There are several etiologic factors involved in the pathogenesis of acne vulgaris . Therefore, current treatment guidelines recommend applying different classes of medications for it. This makes medication adherence a challenging issue in acne patients. The current study was designed to assess medication adherence and its possible associated factors in patients with acne vulgaris. This study was performed on patients with acne vulgaris in two dermatology clinics of Imam Khomeini Hospital and Razi Hospital. A validated questionnaire (ECOB, Elaboration d'un outil d'evaluation de l'observance des traitements medicamenteux) was applied to evaluate adherence to topical and oral therapies. We assessed relationship between patients' medication adherence and their sociodemographic, medication, and medical histories. A total of 200 patients, 136 females (68%), and 64 males (32%), with a mean age of 22 years were entered into the study. Overall, only 30 out of 200 patients (15%) were adherent to their treatments. Based on the bivariate analyses, food exacerbations, and severity of the disease by the patient's opinion was significantly associated with overall medication adherence ( P = .03). Moreover, patients who were more adherent to topical treatment were more adherent to systemic treatment, as well ( P = .007). The current study showed that treatment adherence was very low among patients with acne vulgaris. It is recommended to educate patients on the proper use of anti‐acne medications. Besides, it is highly recommended that physicians and pharmacists use ECOB questionnaire regularly to guide patients accurately with the use of their drug regimens.